2005
DOI: 10.1242/jcs.01734
|View full text |Cite
|
Sign up to set email alerts
|

Vinculin acts as a sensor in lipid regulation of adhesion-site turnover

Abstract: The dynamics of cell adhesion sites control cell morphology and motility. Adhesion-site turnover is thought to depend on the local availability of the acidic phospholipid phosphatidylinositol-4,5-bisphosphate (PIP2). PIP2 can bind to many cell adhesion proteins such as vinculin and talin, but the consequences of this interaction are poorly understood. To study the significance of phospholipid binding to vinculin for adhesion-site turnover and cell motility, we constructed a mutant, vinculin-LD, deficient in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(149 citation statements)
references
References 56 publications
5
143
1
Order By: Relevance
“…Dystroglycan with a vinexin binding site mutation could not rescue cell spreading in dystroglycan-depleted cells on E3 laminin, suggesting a possible role for the dystroglycan-vinexinvinculin complex in cell spreading. A number of studies on vinculin-depleted and/or mutated cells have also documented a defect in cell spreading on laminin (Varnum-Finney and Reichardt, 1994;Volberg et al, 1995;Chandrasekar et al, 2005), and similarly to dystroglycan-depleted cells, these cells can still form adhesions because of compensatory changes in other adhesion proteins (Volberg et al, 1995). Furthermore, mutations in the regulatory PIP2-binding site in vinculin inhibit radial cell spreading and subsequent cell polarisation, and thus cell motility (Chandrasekar et al, 2005), a phenotype that is similar to that observed in dystroglycan-depleted myoblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dystroglycan with a vinexin binding site mutation could not rescue cell spreading in dystroglycan-depleted cells on E3 laminin, suggesting a possible role for the dystroglycan-vinexinvinculin complex in cell spreading. A number of studies on vinculin-depleted and/or mutated cells have also documented a defect in cell spreading on laminin (Varnum-Finney and Reichardt, 1994;Volberg et al, 1995;Chandrasekar et al, 2005), and similarly to dystroglycan-depleted cells, these cells can still form adhesions because of compensatory changes in other adhesion proteins (Volberg et al, 1995). Furthermore, mutations in the regulatory PIP2-binding site in vinculin inhibit radial cell spreading and subsequent cell polarisation, and thus cell motility (Chandrasekar et al, 2005), a phenotype that is similar to that observed in dystroglycan-depleted myoblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Vcl can regulate the coupling of adhesion sites to the actin cytoskeleton (Chandrasekar et al, 2005), and is also known for binding to cadherin-based cell-cell contact sites through a-and b-catenin (Peng et al, 2010;Weiss et al, 1998). Recently it has been described that ZO-1 recruitment to a-catenin links the assembly of the endothelial barrier to adherens junctions (Maiers et al, 2013).…”
Section: Novel Role Of Vcl In Gap Junctional Communicationmentioning
confidence: 99%
“…The acidic phospholipid phosphatidylinositol (4,5)-bisphosphate [PtdIns(4,5)P 2, PIP 2 ] directly regulates the actin cytoskeleton by modulating the activity and targeting of actin regulatory proteins (Yin and Janmey, 2003). Vcl binds PIP 2 , thereby acting as a sensor that can modify how phospholipids regulate the coupling of adhesion sites to the actin cytoskeleton (Chandrasekar et al, 2005;Palmer et al, 2009). Class I phosphoinositide 3-kinases (PI3Ks) phosphorylate phospholipids including PIP 2 , and act as scaffolding adapters (Costa and Hirsch, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although phosphatidylinositol 4,5-bisphosphate disrupts the intramolecular interaction Vh-Vt (50), it is unlikely that it unmasks the capping domain of Vt, because it also inhibits the binding of Vt to actin filaments (51). The interaction of phosphatidylinositol 4,5-bisphosphate with the C-terminal arm is also known to control the turnover of focal adhesions (52). Whether the regulation of the capping function by phosphatidylinositol 4,5-bisphosphate contributes to the regulation of focal adhesion turnover is an interesting open issue.…”
Section: Mechanism Of Inhibition Of Barbed Endmentioning
confidence: 99%